Specifics in Introduction and Functioning of the Currency Board in Bulgaria - Radukanov, Sergey (Journal of Applied And Theoretical Social Sciences, 2022)
The article studies two main aspects of functioning of the currency board in Bulgaria: its characteristics and its specifics and peculiarities. Concerning the characteristics of the currency board in Bulgaria, the attention is focused on several theoretical matters of the nature of the currency board: mechanism for introduction of the currency board; choosing the foreign currency, to which the local monetary unit is to be fixed; financing the initial currency reserve, in order for the currency board to start functioning; setting the fixed exchange rate to the reserve currency; establishing the amount of coverage of the quantity of cash in circulation by the currency reserves; administration of the currency board; implementation of the function “lender of last resort” in cases of liquidity crisis; supervision of the commercial banks’ operation. Each country is characterized by its specifics in terms of management of public finances, condition of the real (non-financial) sector, service sector, monetary and banking system. These specifics are reflected in the monetary boards, introduced in the individual countries. The article provides a detailed analysis of the specifics of the currency board in Bulgaria. The options for an independent monetary policy of the central bank are heavily restricted, and on the other hand, the currency board attained the goal of its policy – ensuring of price stability. As of the present moment, Bulgaria joined the exchange rate mechanism (ERM II) in 2020 and makes every effort to cover the criteria for real convergence.